Michael acceptor molecules in natural products and their mechanism of action - Liang, Song-Ting; Chen, Chu; Chen, Rui-Xin; Li, Rui; Chen, Wen-Li; Jiang, Gui-Hua; Du, Lei-Lei (Frontiers in Pharmacology, 2022)
Purpose: Michael receptor molecules derived from plants are biologically active due to electrophilic groups in their structure. They can target nucleophilic residues on disease-related proteins, with significant therapeutic effects and low toxicity for many diseases. They provide a good option for relevant disease treatment. The aim of this study is to summarize the existing MAMs and their applications, and lay a foundation for the application of MAMs in life science in the future. Methods: This review summarizes the published studies on Michael receptor molecules isolated from plants in literature databases such as CNKI, Wanfang Data, PubMed, Web of Science, ScienceDirect, and Wiley. Latin names of plants were verified through https://www.iplant.cn/. All relevant compound structures were verified through PubChem and literature, and illustrated with ChemDraw 20.0. Result: A total of 50 Michael receptor molecules derived from various plants were discussed. It was found that these compounds have similar pharmacological potential, most of them play a role through the Keap1-Nrf2-ARE pathway and the NF-κB pathway, and have biological activities such as antioxidant and anti-inflammatory. They can be used to treat inflammatory diseases and tumors. Conclusion: The Michael receptor molecule has electrophilicity due to its unsaturated aldehyde ketone structure, which can combine with nucleophilic residues on the protein to form complexes and activate or inhibit the protein pathway to play a physiological role. Michael receptor molecules can regulate the Keap1-Nrf2-ARE pathway and the NF-κB pathways. Michael receptor molecules can be used to treat diseases such as inflammation, cancer, oxidative stress, etc.